Stock Repurchase as a Takeover Defense - Bagnoli, Mark; Gordon, Roger; Lipman, Barton L. (Review of Financial Studies, 1989)
We develop a model in which stock repurchases serve as a defense against takeovers by signaling the manager’s private information about the value of the firm. The manager repurchases shares to block a takeover only if the cost of doing so is not too high. Since the cost is inversely related to the value of the firm under his management, a repurchase signals that the value of the stock is high, blocking a takeover. While a repurchase increases the expected value of the stock, it also makes the stock riskier. The model also implies that there are too few takeovers for efficiency.